Struktur Kecepatan Gelombang Gempa dan Koreksi Stasiun Seismologi di Indonesia - Nanang T. Puspito (Jurnal Matematika & Sains, 1996)
We have determined the spherically-layered model for P-wave velocity structure and station corrections for seismographic stations in the Indonesian region and its surrounding. The P-wave velocity structure has been developed down to a depth of 700 km while the station corrections have been determined for 35 seismographic stations located in the study region. We inverted the P-wave travel-times data by using the so called "damped least-squares inversion method"1,7). The modeling space is divided into 15 homogeneously layers with the initial velocity model based on the modification from Jeffrey-Bullen6). We employed 13,115 P-wave travel-times data from 459 earthquakes occurring in the period of 1984 to 1988. The data were taken from the bulletin of International Seismological Center (ISC) London. We performed the inversion for 10 iterations. The solutions can be considered to have achieved convergence after the 6-th iteration. The average travel-time residuals were reduced from 0.40 sec to 0.08 sec. The obtained velocity structure model faster than the initial model of Jeffrey-Bullen. The obtained station corrections for seismographic stations in Sumatra and Java show negative values. In the Philippine Islands, Banda Sea, Northern Australia, and Malay Peninsula the obtained station corrections show positive values.